การจำลองเงินออมหลังเกษียณ : กรณีศึกษาสำหรับสมาชิกกองทุนสำรองเลี้ยงชีพของจุฬาลงกรณ์มหาวิทยาลัย - ชนิตา วงษ์แหวน (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
This project is a study of forecasting retirement savings by stochastic process with a case study of Chulalongkorn University’s provident fund. We study and create stochastic forecasting models to predict retirement savings for provident fund members of Chulalongkorn University. We consider various factors that influence the financial situation in the future including salary, academic titles, working age until retirement, percentage of investment (with respect to salary), investment return rate, percentage of accumulated membership funds (with respect to wage), percentage of the employer contribution (with respect to wage), and the salary adjustment in the future. All simulations and analysis are done using Excel.